The impact of smartphone dependence on college students' sleep quality: the chain-mediated role of negative emotions and health-promoting behaviors - Yunfei Tao; Zhaozhi Liu; Li Huang; Haowei Liu; Haodong Tian; Jinlong Wu; Lan Li; Li Peng (Frontiers Media S.A., 2024)
ObjectiveSleep disturbances among college students have become a significant issue affecting their daily lives. This study aims to explore the relationship between smartphone dependence and sleep quality and examine the mediating roles of negative emotions and health-promoting behaviors.MethodsA total of 23,652 college students were included in the study, and 21,314 valid questionnaires were collected. The survey assessed demographic factors, smartphone dependence, sleep quality, negative emotions, and health-promoting behaviors. A chain mediation analysis was conducted to examine the relationships among these factors.ResultsSmartphone dependence was significantly positively correlated with sleep quality (r = 0.272, p < 0.001) and negative emotions (r = 0.414, p < 0.001), and significantly negatively correlated with health-promoting behaviors (r = −0.178, p < 0.001). Sleep quality was positively correlated with negative emotions (r = 0.472, p < 0.001) and negatively correlated with health-promoting behaviors (r = −0.218, p < 0.001).Smartphone dependence was a significant positive predictor of sleep quality. Moreover, negative emotions and health-promoting behaviors influenced the relationship between smartphone dependence and sleep quality. The total effect, direct effect, and indirect effect values were 0.304, 0.122, and 0.170, respectively.ConclusionDifferent demographic factors (such as gender and place of residence) can lead to variations in different variables. Smartphone dependence and negative emotions have a positive impact on sleep quality among college students, while health-promoting behaviors have a negative impact. Smartphone dependence directly and positively affects sleep quality and can also influence it indirectly through the mediating effects of negative emotions and health-promoting behaviors, both individually and in a chain-like manner.